Analisis Kinerja Pemungutan Pajak Bumi dan Bangunan Perdesaan Dan Perkotaan Dinagari Paninjauan - Yenni, Fitri (Asosiasi Dosen Akuntansi Indonesia, 2023)
The purpose of this research is to find out the performance constraints or obstacles faced by tax collectors in collecting Rural and Urban Land and Building Tax (PBB-P2), and to analyze how the performance of rural and urban land and building tax collection in Nagari Paninjauan. The type of research used is field research with qualitative methods. Techniques with data collection used through interviews and documentation. Data analysis techniques were carried out in a qualitative descriptive manner, then described and classified aspects of certain problems and explained through effective sentences. The results of the study indicate that the performance of officers in the implementation of rural and urban land and building tax collection in Nagari Paninjauan has not been carried out effectively there are still tax collectors who have not been able to carry out their duties to the fullest, the unclear schedule for land and building tax collection carried out by officers taxes, tax officials often delay the distribution of SPPT, lack of socialization by tax officials regarding ownership of land data, lack of knowledge about taxes on the part of taxpayers and tax officers. So that tax officers or collectors in Nagari Paninjauan must be more active in conducting tax socialization and establishing tax sanctions so that people are more obedient in paying taxes, especially regional taxes. Besides that, the government in Nagari Paninjauan should review the data collection of taxpayers by updating the data, so that it is clear who is the subject and object of PBB-P2 tax.